2023
DOI: 10.1038/s41586-023-06135-z
|View full text |Cite
|
Sign up to set email alerts
|

Silicon isotope constraints on terrestrial planet accretion

Abstract: Understanding the nature and origin of the precursor material to terrestrial planets is key to deciphering the mechanisms and timescales of planet formation1. Nucleosynthetic variability among rocky Solar System bodies can trace the composition of planetary building blocks2–5. Here we report the nucleosynthetic composition of silicon (μ30Si), the most abundant refractory planet-building element, in primitive and differentiated meteorites to identify terrestrial planet precursors. Inner Solar System differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…Based on Fe isotopes, Hopp et al (2022) recently suggested that Ryugu and the parent body of CI chondrites formed beyond the accretion of most carbonaceous chondrite parent bodies. However, CR and CI chondrites (and/or Ryugu) define nucleosynthetic compositional endmembers among carbonaceous chondrite groups in Si, Fe, and Mg (Schiller et al 2020;Hopp et al 2022;Onyett et al 2023). Although this does not preclude that CR, CI, and Ryugu all accreted in the outermost disk, it is difficult to reconcile with the observation that other carbonaceous chondrites record nucleosynthetic compositions intermediated between the CR and CI chondrites (and/or Ryugu) endmembers.…”
Section: Kinship With the CI Parent Asteroid And The Accretion Region...mentioning
confidence: 98%
See 1 more Smart Citation
“…Based on Fe isotopes, Hopp et al (2022) recently suggested that Ryugu and the parent body of CI chondrites formed beyond the accretion of most carbonaceous chondrite parent bodies. However, CR and CI chondrites (and/or Ryugu) define nucleosynthetic compositional endmembers among carbonaceous chondrite groups in Si, Fe, and Mg (Schiller et al 2020;Hopp et al 2022;Onyett et al 2023). Although this does not preclude that CR, CI, and Ryugu all accreted in the outermost disk, it is difficult to reconcile with the observation that other carbonaceous chondrites record nucleosynthetic compositions intermediated between the CR and CI chondrites (and/or Ryugu) endmembers.…”
Section: Kinship With the CI Parent Asteroid And The Accretion Region...mentioning
confidence: 98%
“…Although our analysis does not allow us to distinguish between 26 Al or Mg isotope heterogeneity to account for the range of μ 26 Mg * composition across chondrite groups and, in particular, Ryugu's μ 26 Mg * excess relative to CIs, future measurements of Ryugu samples may provide insights into this question. Silicon has been recently developed as a novel nucleosynthetic tracer to probe genetic relationships between solar system solids, asteroids, and planetary bodies (Onyett et al 2023). Carbonaceous chondrites record μ 30 Si variability that corresponds to about 23 ppm, with CR and CI chondrite groups defining compositional endmembers.…”
Section: Excess 26 Mg * In Ryugumentioning
confidence: 99%
“…This was taken as instant zero of the age of the solar system. What followed was a complicated series of violent events [2][3][4].…”
Section: Introductionmentioning
confidence: 99%